Improvements of a high-speed focus distance modulated fibrecoupled confocal sensor for nanocoordinate measuring systems - Gröschl, Andreas Christian; Köhnen, Stephan; Schaude, Janik; Hausotte, Tino (SENSOREN UND MESSSYSTEME 19. ITG/GMA-Fachtagung, 2018)
This article presents improvements of a new robust, precise, high-frequency focal-distance-modulated confocal point sensor for probing in coordinate measuring systems (CMS). While maintaining the known advantages of the confocal measurement principle, the sensor represents an innovative combination of a ﬁbre-coupled confocal illumination and detection with a tuneable, acoustically driven gradient-index ﬂuid lens (TAG lens) for modulation of the focus distance andanovelsignalprocessingutilizingalock-inampliﬁer. Thenewarrangementisabletoachieveanapproximatelylinear characteristiccurvefortheoptimisedfeedbackcontroloftheCMSinscanningsamplemode. Thisarticleemphasisesthe improvement of the lock-in ampliﬁcation by using a custom signal processing on the basis of a ﬁeld programmable gate array (FPGA).<br